Cultures of healing - Horden, Peregrine, author.
1 online resource.
Keywords: This volume brings together for the first time an updated collection of articles exploring poverty, poor relief, illness, and health care as they intersected in Western Europe, the Mediterranean and the Middle East, during a 'long' Middle Ages. It offers a thorough and wide-ranging investigation into the institution of the hospital and the development of medicine and charity, with focuses on the history of music therapy and the history of ideas and perceptions fundamental to psychoanalysis. The collection is both sequel and complement to Horden's earlier volume of collected studies, Hospitals and Healing from Antiquity to the Later Middle Ages (2008). It will be welcomed by all those interested in the premodern history of healing and welfare for its breadth of scope and scholarly depth.